Determination of chlorine in cement via CaCl molecule by high-resolution continuum source graphite furnace molecular absorption spectrometry with direct solid sample analysis - Bechlin, Marcos A. [UNESP]; Ferreira, Edilene C. [UNESP]; Gomes Neto, José A. [UNESP] (Elsevier, 2017)
The use of a new molecule the calcium mono-chloride (CaCl) with absorption band head at 621.145 nm was evaluated in the development of a method for Cl determination in cement by high-resolution continuum source graphite furnace molecular absorption spectrometry (HR-CS GFMAS) employing direct solid sample analysis. Calcium compounds present in cement samples acted as CaCl-forming reagent. Pyrolysis and vaporization curves were established to optimize the atomizer temperature program. The optimum pyrolysis and vaporization temperatures were 1000 °C and 2200 °C, respectively. These values provided higher thermal stability of the CaCl molecule which allows reducing matrix effects and the calibration with aqueous standard solutions in the range of 10–200 ng Cl. Correlation coefficient of 0.995 and a slope of 0.00159 s ng− 1 were obtained, with a calculated limit of detection of 1.4 ng Cl. Sample masses in the range 0.65–1.05 mg can be accurately weighed and assayed. Commercial cement samples were analyzed by the proposed method and the concentrations of Cl were in the 159–540 μg g− 1 concentration range. Samples were also analyzed by the Brazilian Association of Technical Norms (ABNT) and results were in agreement at a 95% confidence level (paired t-test). Recoveries of Cl added to samples were in the range 101–118% and the relative standard deviations (n = 12) were in the 3.4–11.2% interval.
Keywords: Calcium mono-chloride; Cement; Chlorine; Direct solid sample analysis; High-resolution continuum source graphite furnace molecular absorption spectrometry